(untitled) (Comparative & International Education Series, 2022)
The purpose of this chapter is to ground the conversation about international graduate students in the scholarly literature using key constructs, central theories, and themes that illuminate the issues associated with their socialization in U.S. higher education. Traditional Western concepts of socialization have relied on something that was "done" to students rather than students being active participants in the process. Further, much of what has been written about socialization in U.S. higher education has not focused on international doctoral student experiences, even though a large body of literature focuses on international undergraduate students.